The Influence of BMX Gene Polymorphisms on Clinical Symptoms after Mild Traumatic Brain Injury. (22nd April 2014) - Wang, Yu-Jia; Hsu, Yu-Wen; Chang, Che-Mai; Wu, Chung-Che; Ou, Ju-Chi; Tsai, Yan-Rou; Chiu, Wen-Ta; Chang, Wei-Chiao; Chiang, Yung-Hsiao; Chen, Kai-Yun
Abstract : Mild traumatic brain injury (mTBI) is one of the most common neurological disorders. Most patients diagnosed with mTBI could fully recover, but 15% of patients suffer from persistent symptoms. In recent studies, genetic factors were found to be associated with recovery and clinical outcomes after TBI. In addition, results from our previous research have demonstrated that the bone marrow tyrosine kinase gene in chromosome X (BMX), a member of the Tec family of kinases, is highly expressed in rats with TBI. Therefore, our aim in this study was to identify the association between genetic polymorphisms of BMX and clinical symptoms following mTBI. Four tagging single nucleotide polymorphisms (tSNPs) of BMX with minimum allele frequency (MAF) >1% were selected from the HapMap Han Chinese database. Among these polymorphisms, rs16979956 was found to be associated with the Beck anxiety inventory (BAI) and dizziness handicap inventory (DHI) scores within the first week after head injury. Additionally, another SNP, rs35697037, showed a significant correlation with dizziness symptoms. These findings suggested that polymorphisms of the BMX gene could be a potential predictor of clinical symptoms following mTBI.